National adoption of video-assisted thoracoscopic surgery (VATS) lobectomy: the Italian VATS register evaluation - Divisi, Duilio; Bertolaccini, Luca; Barone, Mirko; Amore, Dario; Argnani, Desideria; Zaccagna, Gino; Solli, Piergiorgio; Di Rienzo, Gaetano; Curcio, Carlo; Crisci, Roberto; Group, Italian VATS (Journal of Thoracic Disease; Vol 10, No 1 (January 31, 2018): Journal of Thoracic Disease, 2018)
Background: The expertise curve of video-assisted thoracoscopic surgery (VATS) lobectomies still stirs debate and controversy both because of the number of procedures to carry out and of the evaluation of the learning threshold. The purpose of our study was the examination of the variables related to the learning curve of the video-assisted approach, to establish what may be an expression of the technical maturity of the surgeon. Methods: The National Register for VATS lobectomy built in 2013 was used to collect data from 65 Thoracic Surgery Units. Out of more than 3,700 patients enrolled, only information from Units with ≥100 VATS lobectomies were retrospectively analysed. Unpaired Student’s t-tests, Fisher’s exact tests, Pearson’s χ2 were applied as needed. Cumulative summative analysis and one-way ANOVA were used to identify the expertise curve of VATS lobectomy. Results: Ten institutions contributed a total of 1,679 patients, who were divided into three uniform groups according to the chronological sequence of surgery. The length of utility incision, the number of dissected lymph nodes and the operative time were not statistically significant (P=0.999, P=0.972 and P=0.307, respectively) among groups. Conversion to thoracotomy and postoperative air leaks occurred in 125 (7.44%) and 109 (6.49%) patients, gradually declined in Group 3 with statistical signi cance (P=0.048 and P=0.00086). Conclusions: The conversion rate and the percentage of air leaks seem to de ne the expertise of VATS lobectomy, being linked to the ability to manage more complicated surgical cases or intraoperative adverse events.